2017
DOI: 10.1096/fj.201700025r
|View full text |Cite
|
Sign up to set email alerts
|

Maternofetal transport of vitamin B12: role of TCblR/CD320and megalin

Abstract: Vitamin B deficiency causes megaloblastic anemia and neurologic disorder in humans. Gene defects of transcobalamin (TC) and the transcobalamin receptor (TCblR), needed for cellular uptake of the TC-bound B, do not confer embryonic lethality. TC deficiency can produce the hematologic and neurologic complications after birth, whereas TCblR/ gene defects appear to produce mild metabolic changes. Alternate maternofetal transport mechanisms appear to provide adequate B to the fetus. To understand this mechanism, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
(74 reference statements)
2
13
0
Order By: Relevance
“…Under our experimental conditions, Ds-RED-holo-TC segregated to the surface of the cell and underwent internalization within 2 h (Fig. 1C), as previously documented in other cell types (15,46). Immunodetection of CD320 receptor indicated low levels of soluble CD320 in the conditioned culture medium and substantial amounts of the receptor in whole-cell extracts of BAECs (Supplemental Fig.…”
Section: Secretion Of Apo-tc Uptake Of Holo-tc and Expression Of CDsupporting
confidence: 81%
See 1 more Smart Citation
“…Under our experimental conditions, Ds-RED-holo-TC segregated to the surface of the cell and underwent internalization within 2 h (Fig. 1C), as previously documented in other cell types (15,46). Immunodetection of CD320 receptor indicated low levels of soluble CD320 in the conditioned culture medium and substantial amounts of the receptor in whole-cell extracts of BAECs (Supplemental Fig.…”
Section: Secretion Of Apo-tc Uptake Of Holo-tc and Expression Of CDsupporting
confidence: 81%
“…Endocytosis and transcytosis of holo-TC have also been proposed as important mechanisms for the mobilization of maternal Cbl in the placenta (42)(43)(44)(45). Investigation of maternofetal Cbl transfer in a CD320 knockout mouse model showed that, in the absence of a functional CD320 receptor, Cbl could be supplied to the fetus by uptake of holo-TC by megalin, a multiligand receptor (46).…”
mentioning
confidence: 99%
“…The importance of these receptors in supporting cellular proliferation was emphasized when antibodies directed against MEG and CUBAM, but not TC-R, caused fetal demise after their injection into pregnant mice [35]. Correspondingly, murine TC-R knock-out fetuses survived only until birth due to MEG maintaining maternofetal transport of Cbl in the visceral yolk sac and therefore Cbl uptake within fetal brain, spinal cord, and renal tissue in utero [36].…”
Section: Cbl Uptake In Breast Tumors Independent Of the Tc:tc-r Pathwaymentioning
confidence: 99%
“…of Cd320 2/2 mice corrected some of the hematologic parameters, such as HGB, HCT, and RDW but did not correct or worsen the neuropathology. Although, the levels of Cbl in the Cd320 2/2 mouse liver and spleen were lower, they were not as severely depleted as in the brain and SC, suggesting an alternate pathway for Cbl uptake in these organs if additional Cbl is available through diet (23,24). Furthermore, lack of Cbl uptake in the CNS of the Cd320 2/2 mouse fed a normal diet contributes to elevated TC-Cbl in the blood and results in increased Cbl in the kidneys via uptake by megalin (3).…”
Section: Discussionmentioning
confidence: 90%
“…Six groups of C57BL/6J wild-type (Cd320 +/+ ) and TCblR/Cd320knockout (Cd320 2/2 ) [C57BL/6J-Cd320Gt(pGt01xft2)Qua] mice, 5-mo-old males and females (1:1 ratio), backcrossed twice on a C57BL/6J background, were used. The age of the mice for the study was based on the observation of severe CNS Cbl deficiency in the Cd320 2/2 mice and systemic Cbl deficiency after 3 mo of consuming a Cbl-deficient diet and the observation of behavioral deficits in 5-mo-old mice (23,24). The wild-type C57BL/6J mice (Cd320 +/+ ) used in the study were derived from a wild-type litter, and the Cd320 2/2 were generated by breeding homozygous mice.…”
Section: Methodsmentioning
confidence: 99%